Rancang Bangun Sistem Smart Posbindu Peyakit Tidak Menular (PTM) Berbasis Android untuk Deteksi Dini dan Monitoring Kesehatan Masyarakat - Maulana, Much. Rifqi; Royanti, Nur Ika; Winoto, Ratno Aji (LogicLink, 2025)
The rapid increase in internet usage (62%) and mobile phone ownership (90%) in Indonesia indicates the significant potential of digital technology to support health services. The Integrated Non-Communicable Disease Health Post (Posbindu PTM) in Mojo Village plays an essential role in early detection and community health monitoring. However, its implementation still faces several challenges, including manual schedule announcements, data recording errors and loss risks, as well as limited dissemination of health information and education. This study aims to design and develop a mobile Smart Posbindu PTM application based on Android as a digital solution to enhance the effectiveness of Posbindu services. The application was developed using the Dart programming language with the Flutter framework and Supabase as the database. Its main features include schedule notifications, digital data recording, fast and accurate reporting, health history monitoring, and educational information related to non-communicable diseases. The system development method used in this study is the Waterfall model, consisting of requirements analysis, system design, implementation, testing, and maintenance stages. Data were collected through interviews with midwives and Posbindu cadres, direct observation, and questionnaires distributed to Posbindu participants. The application was tested using User Acceptance Test (UAT) methods to ensure functionality and user satisfaction. The results show that the Smart Posbindu PTM application was successfully developed and functioned properly according to user needs. This application provides significant benefits by improving data management efficiency, accelerating reporting, facilitating health record monitoring, and supporting health education and information accessibility for the community.